DIMENSI HAM DAN HUKUM ISLAM DALAM PUTUSAN MAHKAMAH KONSTITUSI NO. 46/PUU-VIII/2010 - Imam Mustofa (Millah: Journal of Religious Studies, 2012)
This paper describes the dimensions of Human Right (HAM) enforcement in the Constitutional Court decision of number 46/PUU-VIII/2010. Two important things which are considered because law discourse development, especially the law of marriage in Indonesia resembling Constitutional Court's decision of number 46/PUU-VIII/2010 that affirmed protection of human rights of all citizens backgrounds without primordial. The result of the analysis is expected to create a comprehensive understanding of the human rights dimension of the Constitutional Court's decision of number 46/PUU-VIII/2010 and create an objective and comprehensive understanding that the decision was not contrary to the provisions of Islamic law.